Endocrinology of osmoregulation and thermoregulation of Australian desert tetrapods: A historical perspective. - Cooper, Christine (2015)
Many Australian tetrapods inhabit desert environments characterised by low productivity, unpredictable rainfall, high temperatures and high incident solar radiation. Maintaining a homeostatic milieu intérieur by osmoregulation and thermoregulation are two physiological challenges faced by tetrapods in deserts, and the endocrine system plays an important role in regulating these processes. There is a considerable body of work examining the osmoregulatory role of antidiuretic hormones for Australian amphibians, reptiles and mammals, with particular contributions concerning their role and function for wild, free-living animals in arid environments. The osmoregulatory role of the natriuretic peptide system has received some attention, while the role of adrenal corticosteroids has been more thoroughly investigated for reptiles and marsupials. The endocrinology of thermoregulation has not received similar attention. Reptiles are best-studied, with research examining the influence of arginine vasotocin and melatonin on body temperature, the role of prostaglandins in heart rate hysteresis and the effect of melanocyte-stimulating hormone on skin reflectivity. Australian mammals have been under-utilised in studies examining the regulation, development and evolution of endothermy, and there is little information concerning the endocrinology of thermoregulation for desert species. There is a paucity of data concerning the endocrinology of osmoregulation and thermoregulation for Australian desert birds. Studies of Australian desert fauna have made substantial contributions to endocrinology, but there is considerable scope for further research. A co-ordinated approach to examine arid-habitat adaptations of the endocrine system in an environmental and evolutionary context would be of particular value.